Assessment of selected heavy metals (Pb,Cd, and Cu) in different species of molluscs and crustaceans from Batan bay, Aklan. - Serrano, Luster May N.
Shelfish consumption has potential health benefits, but the ability of this organism to accumulate heavy metals has raised concerns on public health and thus became the subject of monitoring and risk assessment researches. In this study, the levels of heavy metals in soft tissues of 19 commercially available species of molluscs and crustaceans from Batan Bay, Aklan were determined using flame atomic absorption spectroscopy (FAAS). Results show that concentrations of heavy metals determined ranged from Belo Detection Limit (BDL) - 3.13 mg/kg wet weight (ww) for Pb, 0.42-139.95 mg/kg ww for Cu, and 0.026-1.700 mg/kg ww for Cd. Copper concentrations were notably high in the soft tissues of the three gastropod molluscs namely: Nassarius olivaceus (139.95 mg/kg ww), Chicoreus maurus (45.13 mg/kg), and Telescopium telescopium (33.73 mg/kg), which were above the 30 ug/kg wet weight safety limit imposed by FAO. On the other hand , Pb and Cd concentrations in the soft tissues of all the shellfishes investigated were within the FAO and HACCP safety limits. In general, the calculated exposure doses of Pb, Cu, and Cd through ingestion of anyone of these shellfishes do not exceed the Tolerable Daily Intake (TDI) for the three metals and therefore, were not expected to cause adverse health effects for the general population.